FAKTOR-FAKTOR PENYEBAB IBU RUMAH TANGGA TIDAK MENGIKUTI KEGIATAN MAJELIS TAKLIM DI MASJID DARRUNNUR KELURAHAN TANGKERANG TIMUR KECAMATAN TENAYAN RAYA - Juliana '; Murni Baheram Baheram; Jasfar Jas Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study is motivated High Low to know more clearly Causes Housewife not Following Activity Majelis Taklim in mosque Darrunnur Kelurahan Tangkerang Timur Kecamatan Tenayan Raya. The research problems Which of these is the more dominant factor among factors with External Causes Internal Housewife not Following Activity Majelis Taklim in mosque Darrunnur Kelurahan Tangkerang Timur Kecamatan Tenayan Raya Kota Pekanbaru? The purpose of this study was to determine To find a more dominant factor among factors with External Causes Internal Housewife not Following Activity Majelis Taklim in mosque Darrunnur Kelurahan Tangkerang Timur Kecamatan Tenayan Raya. The population in this study as many as 55 people and the sample 35 members Majelis Taklim the sample used is nonprobability sampling using a sample of saturated Instrument collecting data questionnaire with 37 statements and after the trial lived 34 valid statement to be made in the research instrument. Data analysis through quantitative descriptive analysis. Presentation of the answers obtained from the calculation results based on indicators of internal factors to a high of 65.29% and based aspects External factors with a high of 64.06%. Sub indicators of Internal Factors The most dominant cause of housewives do not take part majelis taklim Factors which Fatigue with a percentage of 72.14% is classified as High While Sub indicator of External Factors The most dominant cause of housewives do not take part majelis taklim namely Factor Relation Between Family Members with a percentage of 74.22% is classified as High. So it can be concluded that the Most Dominant Factor Factor Between Internal and External Factors Internal Factors that are considered high with a percentage of 65.29% with Sub Indi,cator Fatigue factor of 74.22% were classified as High. Kata Kunci Factor, Causes Housewife, do not follow Activity Majelis taklim